Identification of miR-9-5p as direct regulator of ABCA1 and HDL-driven reverse cholesterol transport in circulating CD14+ cells of patients with metabolic syndrome. Issue 8 (23rd March 2018) - D'Amore, Simona; Härdfeldt, Jennifer; Cariello, Marica; Graziano, Giusi; Copetti, Massimiliano; Di Tullio, Giuseppe; Piglionica, Marilidia; Scialpi, Natasha; Sabbà, Carlo; Palasciano, Giuseppe; Vacca, Michele; Moschetta, Antonio
Abstract: Aims: Metabolic syndrome (MS) is a cluster of cardio-metabolic risk factors associated with atherosclerosis and low-grade inflammation. Using unbiased expression screenings in peripheral blood mononuclear cells, we depict here a novel expression chart of 678 genes and 84 microRNAs (miRNAs) controlling inflammatory, immune and metabolic responses. In order to further elucidate the link between inflammation and the HDL cholesterol pathway in MS, we focussed on the regulation of the ATP-binding cassette transporter A1 (ABCA1), a key player in cholesterol efflux (CE). Methods and results: ABCA1 mRNA levels are suppressed in CD14 + cells of MS patients and are negatively correlated to body mass index (BMI), insulin-resistance (HOMA-IR) and cardiovascular risk, and positively to HDL cholesterol and CE. miRNA target in silico prediction identified a putative modulatory role of ABCA1 for the nuclear factor kappa-light-chain-enhancer of activated B cell (NF-κB) target miR-9-5p, whose expression pattern was up-regulated in CD14 + cells of MS patients, positively correlated to BMI, HOMA-IR, and triglycerides, and negatively to ABCA1 mRNA levels, HDL cholesterol and CE. Ectopic gain and loss of miR-9-5p function in macrophages modulated ABCA1 mRNA and protein levels, ABCA1 miRNA 3'-untranslated region target sequence reporter assay, and CE into HDL, thus confirming ABCA1 as a target of miR-9-5p. Conclusions: We identified the NF-κB target miR-9-5p as a negative regulator of ABCA1 adding a novel target pathway in the relationship between inflammation and HDL-driven reverse cholesterol transport for prevention or treatment of atherosclerosis in MS.